Aspek Geodetik Penegasan Batas Darat Indonesia dan Papua New Guinea: Status dan Permasalahannnya - Silvester Sari Sai; Hasanuddin Z. Abidin; Sobar Sutisna (Institute for Research and Community Services (LPPM) ITB, 2005)
Technical problems of land boundary between Indonesia and Papua New Guinea are related to delimitation and demarcation process that has been done by two countries. The process did not explicitly the datum and reference frame being used in reconstructing of monuments border pursuant to the agreement of meridian in article-1 of boundary agreement of 1973. The uncertainty about the datum caused demarcation process has been done using different datum. The datums are astronomic and geodetic datum. The combination of the coordinate derives from respectively datum to reconstruct the agreement of meridian caused technical problems and implication to status of land boundary of both countries. This paper investigates about status and technical problems of land boundary between Indonesia and Papua New Guinea and its alternative solution. Investigation is done using the boundary monuments coordinate given by GPS survey of 2004 and boundary monuments coordinate pursuant to boundary agreement of 1973 and result of demarcation survey of 1983-1991. This paper is sum up with some conclusions and recommendation.